(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Psychogenic vomiting is a condition characterized by recurrent vomiting without an identifiable organic cause. This case is of a 19-year-old female who presented with non-projectile vomiting following meals and associated depressive symptoms. Multiple medical consultations failed to identify an organic cause for her condition. Treatment consisted of a combination of medication and psychotherapeutic interventions. Gradually, the patient experienced complete resolution of vomiting episodes and significant alleviation of depressive symptoms. This case report sheds light on the challenges in diagnosing and managing psychogenic vomiting, emphasizing the importance of considering psychiatric factors in such cases. Importantly, this case contributes to the limited literature available on psychogenic vomiting.